A rapid ecological assessment for necrophagous flies (Diptera, Calyptratae) in a mosaic landscape of the Colombian Andes (2021)
A necrophagous flies ensemble (Diptera, Calyptratae) was rapidly assessed in four coverages of an anthropogenic landscape in the east range of the Colombian Andes. Ninety- seven individuals belonging to eight species were collected in only two hours of sampling. The highest diversity values and the occurrence of asynanthropic flies in the forest under conservation management may reflect a positively natural restoration process in the area assessed. Grassland, rural and urban coverages were similarly low in diversity and composition. A brief discussion about the flies’ bionomy and their environment association is offered. Necrophagous flies ensembles by coverage behave as an indicator of the anthropic impact on the landscape.